1975
DOI: 10.1002/app.1975.070190503
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance and stereoregularity of PVC

Abstract: SynopsisThe decoupled a-proton spectrum of PVC was examined using a 220 MHz NMR spectrometer. All of the ten possible pentads were detected and an assignment is given based on Bernoullian statistics. This assignment is in general agreement with conclusions reached by previous workers except for some modifications in the heterotactic resonances. Triad tacticity data were obtained from the pentads and were used to estimate the differential enthalpy and entropy changes for bulk PVC polymerized in the temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Syndiotactic segments are more rigid in the glassy state (39) or in solution, and ·conversion level between 0.06 and 0.79 was found tobe without influence (37). From the previous results it has been postulated that aggregates originate from molecular entanglements favored by long chains, and by kinks as a secondary factor (40). These two factors could explain the growing tendency of PVC to aggregate with diminishing polymerization temperature.…”
Section: Solution Properties and Aggregatesmentioning
confidence: 84%
See 1 more Smart Citation
“…Syndiotactic segments are more rigid in the glassy state (39) or in solution, and ·conversion level between 0.06 and 0.79 was found tobe without influence (37). From the previous results it has been postulated that aggregates originate from molecular entanglements favored by long chains, and by kinks as a secondary factor (40). These two factors could explain the growing tendency of PVC to aggregate with diminishing polymerization temperature.…”
Section: Solution Properties and Aggregatesmentioning
confidence: 84%
“…(less for low temperature polymerized PVC) is representative of short chain branching; tertiary chlorine atomsarenot detected, their nurober is at most equal to that of long brailches since they From the abundance of syndiotactic, isotactic and heterotactic triads it is possible to check whether the statistics is Bernoullian (no effect by the penultimate unit). Mitani (28) found no deviation from Bernoullian statistics but Pham (27) and Adel-Alim (26) found it non-Bernoullian outside the 30° -50° range of polymerization temperature. Inoue (29) has shown that the spin-lattice relaxation time T 1 of 1 3c is the same irrespective of the tactic configuration and of the molecular weight, so the intensities of the observed 13c resonances are directly related to the real concentration of carbon atoms in each configuration as for instance for-the tetrads measured by Carman (30).…”
Section: Short Branchesmentioning
confidence: 99%
“…Table I shows the variation of the different persistence ratios with polymerization temperature for poly(viny1 chloride) . 20 A t lower polymerization temperatures, there is an increasing tendency to switch more often between isotactic and syndiotactic placements. Accord- ingly, the average tactic sequences will be shorter and the average number of kinks will be higher than the corresponding Bernoullian case.…”
Section: Resultsmentioning
confidence: 99%
“…The configuration and conformation of PVC in solution have been studied extensively with 1 H and 13 C NMR 7–14. However, the 13 C NMR spectra have shown some advantage over 1 H NMR spectra for determining triad and tetrad concentrations.…”
Section: Introductionmentioning
confidence: 99%